The Queen's House - Jones, Inigo
The influence and complete understanding of Palladian architecture can be seen in this interior view of the central court with its fine windows and geometric marble floor in the Italian manner. The Queen's House sets standards which were maintained by ten generations of English architects. Up to this point, each building had been a challenge to its builders, carpenters, and masons. Each sought to demonstrate his special talents, whether the individual attempt contributed to the whole or not. Now, with the change from Gothic attitudes, the entire piece had a quiet, ordered symmetry about it.